Long‐term psychiatric disorders in families of severe COVID‐19 patients - Kasumi Shirasaki; Toru Hifumi; Moe Sekiguchi; Shutaro Isokawa; Yusuke Nakao; Shinobu Tanaka; Shinsuke Hashiuchi; Ryosuke Imai; Norio Otani (Acute Medicine & Surgery)
Abstract Aim The present study aimed to describe in detail the changes to and assess the risk factors for poor long‐term outcomes of psychiatric disorders in families of COVID‐19 patients. Methods A single‐center, retrospective study using questionnaires. Family members of patients admitted to the intensive care unit (ICU) with severe COVID‐19 participated. Psychiatric disorders refer to the psychological distress such as anxiety, depression, and posttraumatic stress disorder (PTSD) experienced by the patient's family. Results Forty‐six family members completed the survey and were analyzed. Anxiety, depression, and PTSD occurred in 24%, 33%, and 2% of family members, respectively, and psychiatric disorders occurred in 39%. On multivariable analysis, living in the same house with the patient was independently associated with a lower risk of psychiatric disorders in families of COVID‐19 patients (OR, 0.180; 95% CI, 0.036–0.908; p = 0.038). Furthermore, four family members overcame psychiatric disorders, and six family members newly developed psychiatric disorders during the one‐year follow‐up period. Conclusion Approximately 40% of family members had long‐term psychiatric disorders, and some of them overcame the psychiatric disorders, and some newly developed psychiatric disorders over the one‐year follow‐up. Living in the same house with the patient was possibly significantly associated with the reduction of long‐term symptoms of psychiatric disorders, but this result must be interpreted with care. Further large studies are needed to examine the factors associated with the long‐term mental status of family members.